Urgensi Undang-Undang Perlindungan Data Pribadi dalam Pengembangan Kebijakan e-Government di Indonesia - Habibie Hendra Carlo; Fajar Bambang Hirawan (Universitas Medan Area, 2022)
The aim of this article is to identify Urgency of the Law of Privacy Data Protection in Developing E-Government Policy in Indonesia. This Research is focused on the important effect of Privacy Data Protection policy in e-Government development. This problem analized with the theory corcening of e-Government, trust dimension of e-Government, and Privacy Data Protection. The data collected based on desk study and will be analyzed by Qualitative methods. This Article conclude that there is an urgency of the law of privacy data protection to increase the public trust and participation to e-Government system. The Law and Regulation that already applied is not enough to guarantee the privacy data protection and only become the preventive tools because this law and regulation has not been able to give penal sanction to the suspect of illegally used of privacy data protection and the parties that neglect to protect privacy data protection. Therefore, Central Government need to enacted Law of Privacy Data Protection immidiatelly to guarantee data privacy protection in the implementation of e-Government.